PROBLEMATIKA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Huda, Khoirul (IAIN Tulungagung, 2016)
Madrasah is a public educational institution distinctively Islamic. Since the issuance of Â the decree of the Minister and Law No. 3 2/1989 on National Education System, the school is entrusted to manage the education and follow the success of Â the 9-year compulsory education program. Although the school has held the same position with the public schools, but school achievement is still low. The focus of this paper is an internal problem which includes students, teachers, curriculum, resources and infra structure, and aims to determine the efforts under taken at MAN Rejotangan to overcome the problems faced in order to improve the quality of Islamic education. Research on this paper include descriptive study, based on a qualitative research approach, and review of field belongs to science education research, and if viewed from the place designated as a research field. These results indicate the existence of problems serious enough in MAN Rejotangan, which include educators, either quantitatively or qualitatively, the lack of government budget, input a low level, the source of funds and infrastructure is relatively in adequate, student interest low and parents are less concerned about the education, and the development of resources and infrastructures affordably.Kata Kunci: Problematika Madrasah, Pendidikan Islam, Mutu.